The Use of Scoring Rubrics in University - Hadibarata, Tony; Hidayat, Topik; Kwabena, James (Tecno Scientifica Publisher, 2024)
This study examines the application of scoring rubrics as an evaluative instrument in higher education environments. Specifically, it explores the advantages, validity, and reliability associated with their use. Scoring rubrics provide a systematic and unbiased methodology for assessing various academic assignments, assisting educators in delivering constructive feedback and promoting student development. The study delves into the benefits associated with the utilization of rubrics, which encompass improved levels of transparency, uniformity, and fairness in the grading process. Furthermore, it investigates the validity and reliability of rubrics, ensuring the precision and consistency of evaluation outcomes. Moreover, this study explores the utilization of holistic and analytic rubrics within Malaysian universities, providing an analysis of their individual applications and advantages in the evaluation procedure. In the pursuit of improving assessment methods, institutions are increasingly recognizing the significance of including scoring rubrics as a valuable instrument to facilitate high-quality education and foster student achievement.